The Immunopathology of Giant Cell Arteritis Across Disease Spectra - Robinette, Michelle L.; Rao, Deepak A.; Monach, Paul A. (Frontiers in Immunology, 2021)
Giant cell arteritis (GCA) is a granulomatous systemic vasculitis of large- and medium-sized arteries that affects the elderly. In recent years, advances in diagnostic imaging have revealed a greater degree of large vessel involvement than previously recognized, distinguishing classical cranial- from large vessel (LV)- GCA. GCA often co-occurs with the poorly understood inflammatory arthritis/bursitis condition polymyalgia rheumatica (PMR) and has overlapping features with other non-infectious granulomatous vasculitides that affect the aorta, namely Takayasu Arteritis (TAK) and the more recently described clinically isolated aortitis (CIA). Here, we review the literature focused on the immunopathology of GCA on the background of the three settings in which comparisons are informative: LV and cranial variants of GCA; PMR and GCA; the 3 granulomatous vasculitides (GCA, TAK, and CIA). We discuss overlapping and unique features between these conditions across clinical presentation, epidemiology, imaging, and conventional histology. We propose a model of GCA where abnormally activated circulating cells, especially monocytes and CD4+ T cells, enter arteries after an unknown stimulus and cooperate to destroy it and review the evidence for how this mechanistically occurs in active disease and improves with treatment.